The Ruined Elegance : Poems - Sze-Lorrain, Fiona (Book collections on Project MUSE., 2016)
In her new collection, Fiona Sze-Lorrain offers a nuanced yet dynamic vision of humanity marked by perils, surprises, and the transcendence of a "ruined elegance." Through an intercultural journey that traces lives, encounters, exiles, and memories from France, America, and Asia, the poet explores a rich array of historical and literary allusions to European masters, Asian sources, and American influences. With candor and humor, each lyrical foray is sensitive to silence and experience: "I want to honor / the invisible. I'll use the fog to see white peaches."